2004
DOI: 10.1111/j.1365-2567.2004.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection against systemic candidiasis in mice immunized with secreted aspartic proteinase 2

Abstract: Summary Secreted aspartic proteinases (Sap) have been described as virulence factors implicated in the mechanisms of host colonization by the yeast Candida albicans in different types of candidiasis. Intraperitoneal inoculation of C. albicans into BALB/c mice rapidly leads to systemic candidiasis, with significant colonization of the kidneys measurable in the following week. In this study we assessed the potential of vaccination with C. albicans secreted aspartic proteinase 2 (Sap2) in preventing systemic cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 57 publications
(71 reference statements)
3
54
0
Order By: Relevance
“…These results are consistent with those of earlier studies in which anti-enolase antibodies were found to be partially protective in experimental SC (88,89) and supports the notion that other protective mechanisms against SC are also implicated (13)(14)(15)90).…”
Section: Serum Anti-bgl2p Igg Antibodies Are a Novel Independent Diagsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with those of earlier studies in which anti-enolase antibodies were found to be partially protective in experimental SC (88,89) and supports the notion that other protective mechanisms against SC are also implicated (13)(14)(15)90).…”
Section: Serum Anti-bgl2p Igg Antibodies Are a Novel Independent Diagsupporting
confidence: 83%
“…Research efforts currently focus on screening both for Candida cell wall polysaccharides (mannans or ␤-1,3-glucans), extracellular proteins (secreted aspartyl proteinase), cytoplasmic proteins (enolase or heat shock protein 90), metabolites (D-arabinitol), or nucleic acids (DNA or RNA) and for anti-Candida antibodies in body fluids of SC patients (11)(12)(13)(14)(15). The relevance of well defined Candida cell wall proteins or their related antibodies in SC diagnosis, prognosis, and therapy, however, has been barely examined (16 -18).…”
Section: Not Only Does Systemic Candidiasis (Sc)mentioning
confidence: 99%
“…Although the secretion of aspartic proteases has long been recognized as a virulence-associated trait of Candida spp. (38), the vaccinating potential of secreted proteases from Candida (37), and now from Aspergillus, further adds to the biological functions of proteases at the fungus/host interface, as already suggested (39). In this regard, we have recently shown a crucial role for host protease-activated receptors in murine aspergillosis (39).…”
Section: Discussionmentioning
confidence: 89%
“…Different structural microbial Ags such as LPS or the staphylococcal protein A are known to induce polyclonal B cell activation. In addition, several microbial extracellular proteins including enzymes have also been described as B cell activators (8,13,25,51,52). The ability of microbial constituents to induce polyclonal B cell activation in the infected host constitutes a mechanism of host immune evasion used by pathogens to suppress the specific, potentially protective, immune responses (5,14,21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showing that immunization against a particular VIP confers protection against the infection caused by the VIP-producing microbe, further indicates the important role of VIP for the success of microbial colonization (11,(22)(23)(24)(25).…”
mentioning
confidence: 99%